Guidelines for Platform Independent Modeling for Real Time Systems Using UML - Alves, Everton L. G.; Machado, Patricia D. L.; Ramalho, Franklin (Anais do Simpósio Brasileiro de Componentes, Arquiteturas e Reutilização de Software (SBCARS); 2011: Anais do V Simpósio Brasileiro de Componentes, Arquiteturas e Reutilização de Software, 2011)
Real-time systems (RTS) have, as main characteristics, the need of satisfying time constraints while their behavior is executing. RTS are usually reactive, concurrent and deals with both synchronous and asynchronous events. Those properties end up making modeling a very important activity to enable the satisfaction of the requirements and timing constraints. This work shows a way of modeling soft real-time systems using UML 2 at platform independent level. Even though there are other UML extensions for RTS modeling, they deal with low level concepts, not suitable to be used at the independent level context. A set of artifacts are proposed in this work: a UML profile for RTS modeling, ii) a UML package with architectural elements, and iii) a set of guidelines for modeling RTS using UML. The proposed guidelines were evaluated by three case studies. The results showed that the guidelines help to design more complete RTS models.